(untitled) (Journal of Science, Technology and Innovation Policy, 2024)
COVID-19, which emerged in 2019, was the most recent pandemic, significantly affecting populations worldwide. It led to a global catastrophe, in the aspects of politics, environment, social life, health, and economy. Since therapeutic care had not been able to mitigate the spread of the virus, prevention tactics were adopted, which include movement control orders, lockdown, mandatory distancing, and mask wear. Some of these inevitable severe containment measures have been found to disrupt the global supply chain where the consumer manufacturing sector was affected the most. With the certainty that future disasters will happen in one form or another, and to avoid future disruption, the supply chain management of an organization should be prepared with a resilience plan to be more flexible, dynamic, and agile in ensuring supply chain continuity. One way to achieve this is through management of the logistics in the supply chain. This paper aims to present alternative guidelines and strategies in the form of a contingency plan for disaster resilience and flexible logistics management. A qualitative study was conducted on a consumer electronic goods company located in Malaysia, with a factory in Thailand and retailer distribution centres in Myanmar, Laos, Cambodia, and Malaysia. A thematic analysis of the semi-structured interview results identified seven key impacts of COVID-19 on logistics management. The most critical impacts found are ‘shortage of storage capacity’ and ‘lack of containers’. Meanwhile, necessary qualities required in withstanding disasters were revealed, including ‘the ability to be flexible’, ‘adaptability to new things’, and ‘finding alternative solutions’. Finally, this paper concludes with a proposal of guidelines and strategies for resilience and contingency plan implementation.